2012
DOI: 10.4049/jimmunol.1103661
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Activation of the Unfolded Protein Response in Cystic Fibrosis Airway Cells Contributes to p38 MAPK-Mediated Innate Immune Responses

Abstract: Inflammatory lung disease is the major cause of morbidity and mortality in cystic fibrosis (CF); understanding what produces dysregulated innate immune responses in CF cells will be pivotal in guiding the development of novel anti-inflammatory therapies. To elucidate the molecular mechanisms that mediate exaggerated inflammation in CF following TLR signaling, we profiled global gene expression in immortalized human CF and non-CF airway cells at baseline and after microbial stimulation. Using complementary anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 68 publications
3
51
1
Order By: Relevance
“…Furthermore, blockade of autophagy initiation with 3-MA, which would lead to further CFTR accumulation in the ER, induced proinflammatory responses to FliC (Fig. 3A), consistent with our recent observation that elevated ER stress is present in CF cells and tissues, and predisposed CF airway cells to exhibit hyperinflammatory responses to FliC (19). On this basis, we therefore propose that the specific disruption of autophagosome clearance by FliC in CF cells decreases their ability to deal with their ER stress burden by causing the system to back up, leading to activation of proinflammatory ER stress pathways that amplify subsequent TLRelicited responses.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Furthermore, blockade of autophagy initiation with 3-MA, which would lead to further CFTR accumulation in the ER, induced proinflammatory responses to FliC (Fig. 3A), consistent with our recent observation that elevated ER stress is present in CF cells and tissues, and predisposed CF airway cells to exhibit hyperinflammatory responses to FliC (19). On this basis, we therefore propose that the specific disruption of autophagosome clearance by FliC in CF cells decreases their ability to deal with their ER stress burden by causing the system to back up, leading to activation of proinflammatory ER stress pathways that amplify subsequent TLRelicited responses.…”
Section: Discussionsupporting
confidence: 74%
“…5). We recently demonstrated that ER stress is elevated at baseline in a variety of CF tissues and cell types, causing activation of downstream pathways that synergize with canonical TLR5 signaling to induce exaggerated inflammatory responses to FliC (19). Given that ER stress promotes autophagy as a negative-feedback system to limit misfolded CFTR accumulation in the ER through autophagosome-lysosome-mediated degradation (13,66), we propose that therapeutic interventions that promote normal autophagy in CF cells could potentially limit inflammation by reducing the burden of ER stress in CF cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, overexpression of these miRNAs failed to reduce GPR41 mRNA and protein expression in CFBE41o 2 cells (data not shown), excluding the possibility of regulation of GPR41 expression by these miRNAs. Accumulation of misfolded F508del-CFTR in the ER causes ER stress that activates UPR, a signal transduction pathway to alleviate this stress and restore ER homeostasis (32,45,46). Exposure of 16HBE14o 2 cells to tunicamycin or thapsigargin, well-known inducers of ER stress and UPR, increased protein expression of GPR41 ( Figure 6A), implying that the ER stress and UPR may also, independent of CFTR activity, contribute to GPR41 up-regulation.…”
Section: (A) Cfbe41omentioning
confidence: 99%
“…Global gene expression in immortalized human CF and non-CF airway cells showed an inflammatory gene signature involving MAPK signalling and the hyper-inflammatory phenotype in response to microbial stimulation was found to be dependent on p38 activity [46]. CF lung biopsies showed increased immunoreactivity for p38 MAPK activity markers and CFTR Phe508del/Phe508del airway epithelial cells lines (NuLi) confirmed a further increase in p38 activity when stimulated with P. aeruginosa [47].…”
Section: Discussionmentioning
confidence: 91%